Cross-citation in death penalty cases and the internationalisation of human rights - Garland, R (2015)
This thesis examines why courts in the United States of America (US), India and South Africa refer to foreign law in death penalty cases. To gain an understanding of what drives the apex courts of the US, India and South Africa to cite foreign law when considering domestic death penalty issues, this thesis proposes a three-part matrix to both assess the relevant case law and to analyse the academic literature on cross-citation. Firstly, it will be demonstrated that judges in national courts cross-cite comparative law out of a primary interest in constitutional interpretation. Cross-citation is used in this manner to assist judges in their domestic interpretative tasks. Secondly, it will be illustrated how courts that engage in the citation of foreign law also seek guidance from other jurisdictions as to the content of shared values, such as what type of punishment does not fundamentally and unlawfully violate the right to human dignity. Finally, this thesis assesses to what degree courts from the three selected jurisdictions are additionally referencing or applying a customary international law norm when citing foreign sources. The argument is made that the domestic courts under examination engage with comparative law in the context of a broader transnational normative project, taking the international human rights framework that developed after the Second World War as a key reference point. In doing so, this thesis argues that these courts are at times recognising and developing emerging customary norms, and at other times giving effect to and enforcing applicable international human rights law.